The Effect of Helicobacter pylori Infection, Aging, and Consumption of Proton Pump Inhibitor on Fungal Colonization in the Stomach of Dyspeptic Patients - Massarrat, Sadegh; Saniee, Parastoo; Siavoshi, Farideh; Mokhtari, Reyhane; Mansour-Ghanaei, Fariborz; Khalili-Samani, Saman (Frontiers in Microbiology, 2016)
Background: The importance of coinfection of Helicobacter pylori (H.pylori) and Candida albicans (C. albicans) in the development of gastric diseases is not known. In this study, the frequency of concurrent infection of H. pylori and C. albicans in dyspeptic patients was assessed while considering age, gender, and PPI consumption of patients. Methods: Gastric biopsies were taken from 74 yeast-positive dyspeptic patients and gastric disease, age, gender, and proton pump inhibitor (PPI) consumption of subjects were recorded. One antral biopsy was used for rapid urease test (RUT) and one for H. pylori and yeast cultivation and smear preparation. Bacterial isolates were identified according to spiral morphology and the biochemical characteristics. Yeast isolates were identified on Chromagar and by the Nested-PCR amplification of C. albicans-specific topoisomerase II gene. Twenty-seven biopsy smears were Gram-stained and examined by the light microscope for observing H. pylori and yeast cells. Results: Fifty-four (73%) of patients were >40 year. Of 68 patients with PPI consumption record, 46 (67.6%) consumed PPI (p = 0). Comparison of patients in peptic ulcer group (12, 16.2%) with (6, 8.1%) or without (6, 8.1%) H. pylori or in gastritis group (62, 83.8%) with (25, 33.8%) or without (37, 50%) H. pylori showed no significant difference (p > 0.05). Of the 46 patients who consumed PPI, 13 (17.5%) were H. pylori-positive and 33 (44.6%) H. pylori-negative (p = 0). Ten out of twenty-seven smears showed the occurrence of H. pylori cells, including three with yeast cells. Of the 17 H. pylori-negative smears, three showed the occurrence of yeast cells only. Yeasts stained Gram-positive or Gram-negative and appeared as single or budding cells. Conclusion: The older age and PPI consumption could favor fungal colonization in the human stomach. The occurrence of a considerable number of H. pylori-positive or H. pylori-negative patients with gastritis or peptic ulcer shows that co-infection of Candida and H. pylori or infection of yeast alone could be associated with dyspeptic diseases. The occurrence of yeast cells in gastric biopsies with different Gram's reactions indicates that fungi might change their cell wall components for establishing a persistent colonization in the stomach.